Comparative studies on the effect of silane coupling agent on the mechanical properties of talc-filled styrene butadiene rubber and natural rubber - Alkadasi Nabil A N (Journal of Rubber Research, 2005)
Coupling agent is often used in order to improve adhesion between the polymer binder and inorganic substrate. The use of such agents generally results in an improvement in properties. Most of the previous work involving the study of coupling agents on inorganic surfaces has been conducted with silanes on styrene butadiene rubber and natural rubber as comparative studies. The talc was treated with a silane coupling agent (Si-69). The treatment resulted in enhancement of mechanical properties of composites of the said rubbers. In this study, properties of composites filled with treated and untreated talc (separately) are compared. The properties under consideration were tensile strength, modulus at 100;and 400;, Youngs modulus, hardness, etc. Tensile strength improved by 92;and 204;, while modulus at 400;improved by 500;, 378;and elongation at break improved by 233;. Similarly Youngs modulus improved by 34;and 214;for untreated and treated styrene butadiene and natural rubber.
Keywords: Composites; Coupling agent; Mechanical properties; NR; Silane; Styrene butadiene rubber; Talc